2011
DOI: 10.1097/mca.0b013e328342c760
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c as a prognostic marker in patients undergoing primary angioplasty for acute myocardial infarction

Abstract: HbA1c is an independent predictor of the in-hospital mortality in STEMI treated with primary PCI. Apart from prognostic value, high HbA1c could be used for diabetes mellitus diagnosis, which is supported by ADA definitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…Results from previous studies were controversial [3,8,[10][11][12][13][14]. Considering the different management and treatment strategies [15], the effects that high HbA 1c level have on STEMI patients might differ from other types of CAD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from previous studies were controversial [3,8,[10][11][12][13][14]. Considering the different management and treatment strategies [15], the effects that high HbA 1c level have on STEMI patients might differ from other types of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…After scanning the titles, abstracts, reading full texts and hand searching the reference lists of candidate articles, we finally got 19 prospective studies including a total of 35,994 STEMI patients to evaluate the associations between HbA 1c level and their in-hospital, 30-day and long-term mortality. Among these studies, there were 13 studies from Asia [3,8,10,12,13,[23][24][25][26][27][28][29][30], 5 from Europe [11,[31][32][33][34] and 1 from North America [35]. Detailed information of the eligible studies was shown in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…As discussed before, previous trials designed to answer this question were diverse and reached different conclusions [8,9,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this approach was implemented in previous studies [2,9,11]. Second, the study population was derived from a single-center registry and as such is prone to a lesser degree of diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation